The Innovative Perspective of a judicial provision under the focus of celerity and transparency - Schilling Ferraz , Taís; Trombini Puia Baggio , Cristhiane; Reis Caracas, Jaqueline (Seven Editora, 2023)
This article is based on the Justice 4.0 Program, which proposes an incremental innovation in the Judiciary. It evaluates whether two of the strategic actions that are part of the program – ‘Juízo 100% Digital e Núcleos de Justiça 4.0’, are capable of producing gains in terms of speed and transparency, which are two of the Program’s result indicators. Following the worldwide movement of Revolution 4.0, the program, launched in the context of the Covid-19 pandemic, aims to increase the process of digital transformation of the Judiciary, through the most efficient, swift, and transparent judicial service. With specific procedural data from the TJMT, in the period from 04/02/2022 to 06/09/2022, the study uses deductive methodology and empirical research to investigate and conclude that such actions can produce the expected results, but it needs to establish transparent evaluation indicators and monitoring tools at a national level. It also suggests a research agenda to analyze whether the increase in the judgment capacity, in a shorter time, is able to fulfill the user’s aspirations for social pacification. DOI: https://doi.org/10.56238/tfisdwv1-008